2019
DOI: 10.1017/s0144686x19000928
|View full text |Cite
|
Sign up to set email alerts
|

Healthy retirement begins at school: educational differences in the health outcomes of early transitions into retirement

Abstract: The literature on socio-economic variations in the association between retirement timing and health is inconclusive and largely limited to the moderating role of occupation. By selecting the sample case of Mexico where a sizeable number of older adults have no or very little formal education, this study allows the moderating role of education to be tested properly. Drawing on panel data for 2,430 individuals age 50 and over from the Mexican Health and Aging Study (MHAS) and combining propensity score matching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 82 publications
1
8
0
Order By: Relevance
“…Partly consistent with previous evidence that non-working status and transitions into unemployment and retirement increase the probability of having chronic conditions (Allel et al, 2019; Hessel, 2016; Staudinger et al, 2016), we found that age-related increases in the number of chronic diseases (Kingston et al, 2018; Stenholm et al, 2015) were more pronounced in sequences characterized by weak ties to the labor force through ages 70 to 71. However, men in the late , and surprisingly also men and women in the early and ambiguous retirement sequences, experienced slower increases than individuals in the complete sequence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Partly consistent with previous evidence that non-working status and transitions into unemployment and retirement increase the probability of having chronic conditions (Allel et al, 2019; Hessel, 2016; Staudinger et al, 2016), we found that age-related increases in the number of chronic diseases (Kingston et al, 2018; Stenholm et al, 2015) were more pronounced in sequences characterized by weak ties to the labor force through ages 70 to 71. However, men in the late , and surprisingly also men and women in the early and ambiguous retirement sequences, experienced slower increases than individuals in the complete sequence.…”
Section: Discussionsupporting
confidence: 91%
“…Having more chronic conditions negatively affects labor-market participation of older adults and is associated with transitions to unemployment, disability, and retirement (Cabral et al, 2019; De Boer et al, 2018; Van Zon et al, 2020). Growing evidence suggests that the causal relationship is bidirectional: non-working status and transitions into unemployment and retirement also increase the probability of having one or more chronic conditions (Allel et al, 2019; Hessel, 2016; Staudinger et al, 2016).…”
mentioning
confidence: 99%
“…occupational status, job-related stresses and hazards, job satisfaction, retirement income, SES resources for health maintenance and promotion) as mediators and moderators would be necessary to test whether our participants’ views have broader salience, including how these patterns may vary across country-specific contexts. This emphasis on socio-economic characteristics related to retirement health is consistent with recent research on mental health and retirement among British civil servants (Fleischmann et al ., 2020), the influence of work complexity on post-retirement cognitive function in a Swedish study (Andel et al ., 2016), the moderating role of job complexity on post-retirement cognitive decline in Japan (Kajitani et al ., 2017) and the moderating effect of education on the detrimental health effects of early retirements in Mexico (Allel et al ., 2019). More studies are needed, however, that can test and show influences of various dimensions of social class on varied dimensions of health regarding the retirement transition.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, few studies explore patterns related to these topics in Latin American countries (Fisher et al ., 2016). However, findings from two recent studies in Latin America are consistent with the postulate that retirements that happen too early are detrimental to health (León et al ., 2020; Allel et al ., 2021). These studies also document substantial gender and class variations that have been largely overlooked in existing literature.…”
Section: Health Effects Of Retirement Timingmentioning
confidence: 99%
See 1 more Smart Citation